Att bryta sig igenom: – om åtta takter och deras betydelse i Sibelius femte symfoni - Tykesson, Anders (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2006)
To break its way through – eight bars and their significance in Sibelius’ Fifth Symphony In October 1914 Sibelius wrote in his diary that he had started to seriously work on his Fifth Symphony. Not until five years later the finale version of the symphony had its premiere, preceded by two earlier versions. Already in the second version Sibelius had joined the first and the second of the originally four movements into one. The bridge passage consists of eight bars, which are the culmination of the first part, Tempo molto moderato. At the same time, the second part, Allegro moderato, is born out of this culmination. The initial original motive of the symphony makes a “breakthrough” in the bridge passage, which makes the way for the next part. In letters and in his diary Sibelius wrote about the logic of the musical material as “imperative” to his creative process. The bridge passage in the first movement of the Fifth Symphony seems to be a consequence of the logic; the motive must break its way through the chord-blocks to reach the bright character of the Allegro moderato. Consequently, an interpretation of the symphony should also take its point of departure in this inherent logic – as an organic development from the initial horn signal to the six final chords of the last movement.